Pemodelan Sistem Dinamik untuk Prediksi Intensitas Hujan Harian di Kota Malang - Philip Faster Eka Adipraja; Danang Arbian Sulistyo (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2018)
Malang city located in the highlands that is not spared from the flood disaster which the number of events is increasing every year. This is due to many factors, such as the high intensity of daily rainfall coupled with less optimal infrastructure development. In this case, to mitigate the number of flood events, an easy first step is to predict the daily rain intensity. So that the prediction result can be used by the stakeholders to mitigate flood incident in Malang City in the following years. This study aims to create a simple model in predicting rain intensity over a three year period of 2018-2020. Modeling and simulation are done by using a system dynamics approach that can model the system with complex dynamics. The developed model of rain intensity integrates influencing factors such as humidity and temperature. The rainfall intensity model has validated with the error of E1 value is 3.86% and E2 is 4.13% and with RMSE result indicates the number of 8.4452.